2018
DOI: 10.1016/j.jsat.2018.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of motivational enhancement therapy for alcohol problems in partner violent men

Abstract: This study examined the efficacy of brief alcohol intervention in the context of community-based treatment for partner violence. In a randomized clinical trial, 228 partner-violent men with hazardous or problem drinking were recruited at three Intimate Partner Violence (IPV) treatment agencies and randomly assigned to receive one of two 4-session alcohol interventions: Motivational Enhancement Therapy (MET: N = 110) or Alcohol Education (AE: N = 118). After completing alcohol intervention, participants receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(62 citation statements)
references
References 37 publications
0
62
0
Order By: Relevance
“…Knowledge of allocation concealment was not properly described except for two trials that reported a suitable method to conceal allocation (Kraanen et al, 2013;Stuart et al, 2013). Four trials (33.3%) reported no or incomplete blinding of participants and personnel (Alexander et al, 2010;Bahia, 2016;Murphy et al, 2018;Woodin & O'Leary et al, 2010). In the remaining eight trials (66.7%), the blinding of participants and personnel scores indicate that the risk is unclear due to inadequate description.…”
Section: Quality and Publication Bias Assessmentmentioning
confidence: 99%
“…Knowledge of allocation concealment was not properly described except for two trials that reported a suitable method to conceal allocation (Kraanen et al, 2013;Stuart et al, 2013). Four trials (33.3%) reported no or incomplete blinding of participants and personnel (Alexander et al, 2010;Bahia, 2016;Murphy et al, 2018;Woodin & O'Leary et al, 2010). In the remaining eight trials (66.7%), the blinding of participants and personnel scores indicate that the risk is unclear due to inadequate description.…”
Section: Quality and Publication Bias Assessmentmentioning
confidence: 99%
“…Although a variety of outcome measures were used in the trials, the CTS-2 was used to assess IPV in eight of the included trials and embedded within the TLFB approach for one trial (Murphy et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Kistenmacher (2000) and Palmstierna et al (2012) included samples where 66.7% and 77% of the samples, respectively, were considered 'hazardous drinkers' 1 or dependent on alcohol. Kistenmacher Identification Test (AUDIT) (Murphy et al, 2018;Stuart et al, 2013) and the Short Inventory of Problems (SIP; Miller, Tonigan & Longabaugh, 1995) (Stuart et al, 2013). Drug and alcohol abuse and/or dependence was assessed using the DSM-VI for five trials Easton et al, 2018;Mbilinyi et al, 2011;Satyanarayana et al, 2016;Stuart et al, 2013).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations